Comparison of total ankle replacement and ankle arthrodesis in patients with haemophilia using gait analysis: two case reports. (December 2015) - Dauty, Marc; Gross, Raphael; Leboeuf, Fabien; Trossaert, Marc
Abstract Background Severe hemophilia is an inherited, lifelong bleeding disorder characterized by spontaneous bleeding, which results in painful joint deformities. Currently two surgical treatments are available to treat haemophilia-related ankle joint destruction: ankle arthrodesis and total ankle replacement. The aim of the present study was to compare these two surgical procedures in haemophiliac subjects. Case presentation Kinematic and dynamic parameters were quantified using a three-dimensional gait-analysis system in two similar clinical cases. In Caucasian case 1, ankle arthrodesis was chosen because of a kinematic ankle flexion defect and lack of dynamic power regeneration. The defect in energy absorption was compensated for by the contralateral side. Total ankle replacement in Caucasian case 2 allowed sparing the ipsilateral knee (maximum 0.27 preoperatively vs. 0.71 W/kg postoperatively) and hip joints powers (maximum 0.43 preoperatively vs. 1.25 W/kg postoperatively) because of the small ankle dorsiflexion motion. Conclusions Total ankle replacement is recommended for haemophiliac patients who present with a preserved ankle range of motion.